2006
DOI: 10.1200/jco.2006.24.18_suppl.6596
|View full text |Cite
|
Sign up to set email alerts
|

Serial changes in bone marrow cellularity, reticulin fibrosis and microvessel density in patients with chronic myeloid leukemia (CML) in chronic phase treated with imatinib

Abstract: 6596 Background: Imatinib Mesylate, a BCR-ABL tyrosine kinase inhibitor produces sustained complete hematological response (CHR) in CML patients in chronic phase. There is a paucity of information on the effects of imatinib on the bone marrow (BM) morphology and angiogenesis. We evaluated the sequential changes in these parameters in 22 CML chronic phase patients treated with first line imatinib (400 mg) and compared with 10 controls (non-hematological malignancies). Methods: Trephine BM biopsies were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This suggests an antiangiogenic role of imatinib. Lokeshwar NM et al [26] also observed significant reduction in MVD in CML patients after imatinib therapy (Table 7). Kvasnicka HM et al observed that decrease in microvascularization after imatinib therapy is associated with the reversal of myelofibrosis [27].…”
Section: Discussionmentioning
confidence: 82%
“…This suggests an antiangiogenic role of imatinib. Lokeshwar NM et al [26] also observed significant reduction in MVD in CML patients after imatinib therapy (Table 7). Kvasnicka HM et al observed that decrease in microvascularization after imatinib therapy is associated with the reversal of myelofibrosis [27].…”
Section: Discussionmentioning
confidence: 82%